2008
DOI: 10.4161/hv.4.1.4876
|View full text |Cite
|
Sign up to set email alerts
|

Multi-antigenic DNA immunization using herpes simplex virus type 2 genomic fragments

Abstract: A novel DNA vaccine was generated using genomic fragments of a pathogen as the source of both the antigen coding and regulatory regions. The constructs, termed subgenomic vaccines (SGVs), incorporated genomic DNA sequences up to 45 kbp that encompass 15-20 different genes. The SGVs were developed to generate vaccines capable of expressing multiple genes from a single construct, which could be of great benefit for commercialization. The unique feature of the SGVs is that genes are expressed from their native pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…Hence, it can be postulated that when the CDVH native valence was expressed in the same cell as GPV, it was able to induce a cross boost effect. Similar results have been reported when a mixture of antigens was used [25,26]. This can be explained by the induction of a more robust cytokine environment since it is reported that DNA-based vaccination is highly efficient in inducing T cell responses [27].…”
Section: Discussionsupporting
confidence: 83%
“…Hence, it can be postulated that when the CDVH native valence was expressed in the same cell as GPV, it was able to induce a cross boost effect. Similar results have been reported when a mixture of antigens was used [25,26]. This can be explained by the induction of a more robust cytokine environment since it is reported that DNA-based vaccination is highly efficient in inducing T cell responses [27].…”
Section: Discussionsupporting
confidence: 83%
“…(19,57). Limited studies to characterize the cellular responses elicited by ICP4 in mice have been performed (58,59). Martin et al (59) showed that HSVspecific T cells lysed ICP4-expressing target cells in vitro, but none of the immunized mice generated antigen-specific cytotoxic T cell responses.…”
Section: Discussionmentioning
confidence: 99%